Determinan Penerapan Akuntansi Pertanggungjawaban Terhadap Pengendalian Biaya Pada Badan Layanan Umum Rumah Sakit Umum Daerah Manokwari - Simson Werimon; Mona P. Mokodompit; Subekti Catur Oktarisa (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
This study aims to determine the application of Organizational Structure, Budget Planning, Control Implementation, Reporting in Accountancy Accounting has a significant effect on Cost Control. Independent variables in this study are Organizational Structure, Budget Planning, Implementation of Control, Reporting. While the dependent variable is Cost Control. The population in this study were the Director, Head of Finance, Verification and Accounting Section, Treasury and Budget Section, and Administrative Staff totaling 66 people. The sampling technique used is the method of saturation sampling or census. The data used in this study are primary data obtained directly by means of spreading questionnaires to respondents. The test results of this study indicate that the Organizational Structure and Reporting have a significant effect on Cost Control. While Budget Planning and Implementation of Control does not affect the Cost Control.